Asia bond monitor November 2018. (Metro Manila, Philippines Asian Development Bank, 2018)
This publication reviews developments in East Asian local currency bond markets during the third quarter of 2018 and provides outlook, risks, and policy options. Data suggest that local currency bond yields rose in most economies in emerging East Asia between 31 August and 15 October on the back of continued interest rate hikes by the United States Federal Reserve. Highlights of this publication include a special focus on the impact of the Asian Bond Markets Initiative on the region bond market development and a detailed presentation of results from the Asian Bonds Online annual bond market liquidity survey.
Highlights - - Executive Summary - - Introduction: Bond Yields Rise in Emerging East Asia - - Bond Market Developments in the Third Quarter of 2018 - - Policy and Regulatory Developments - - AsianBondsOnline Annual Bond Market Liquidity Survey - - Assessing the Impact of the Asian Bond Markets Initiative on Bond Market - Development in Asia - - Market Summaries.
Keywords: https://www.adb.org/publications/asia-bond-monitor-november-2021 -- Asia; Bonds -- Asia -- Statistics; Government securities -- Asia; Electronic books